Reasons for Elective Cesarean Section amongst Pregnant Women; A Qualitative Study - Sanavi, Fariba Shahraki (Avicenna Research Institute, 2012)
BACKGROUND: A qualitative study was carried out on 200 pregnant women attending obstetric offices and Imam Ali Women's Clinic in Zahedan, Iran during January 2010 to August 2011. Twenty-nine focus group discussions (FGDs) with 5–8 participants in each group were formed. The study included women in the third trimester of pregnancy with the intention or decision to undergo elective cesarean section. The women's views were explored and analyzed in group sessions. Subsequently, the responses were divided into four major categories. The majority (50%) of the opinions expressed were psychological in origin, or stemmed from low perceived behavioral control, improper subjective norms, or wrong attitudes about vaginal delivery. METHODS: Twenty-nine focus group discussions (FGDs) with 5-8 participants in each group were formed. The study included women in the third trimester of pregnancy with the intention or decision to undergo elective cesarean section. The women's views were explored and analyzed in group sessions. RESULTS: The responses were divided into four major categories. The majority (50%) of the opinions expressed were psychological in origin, or stemmed from low perceived behavioral control, improper subjective norms, or wrong attitudes about vaginal delivery. CONCLUSION: It is necessary to hold psychological skills training classes for pregnant women and their husbands to persuade them attend group discussion sessions to increase their control on perceived behavior, highlight their positive attitudes and direct them toward natural vaginal delivery.